Cardiorespiratory Fitness Is Associated with Selective Attention in Healthy Male High-School Students - Wengaard, Eivind; Kristoffersen, Morten; Harris, Anette; Gundersen, Hilde (Frontiers in Human Neuroscience, 2017)
Abstract Background: Previous studies have shown associations of physical fitness and cognition in children and in younger and older adults. However, knowledge about associations in high-school adolescents and young adults is sparse. Thus, the aim of this study was to evaluate the association of physical fitness, measured as maximal oxygen uptake (V̇O2max), muscle mass, and weekly training, and cognitive function in the executive domains of selective attention and inhibitory control, in healthy male high-school students. Methods: 54 males (17.9 ±0.9 years, 72 ±11kg and 182 ±7cm) completed a V̇O2max test, a body composition test, and a visual cognitive task based on the Posner cue paradigm with three types of stimuli with different attentional demands (i.e. stimuli presentation following no cue, valid cue or invalid cue presentations). The task consisted of 336 target stimuli, where 56 (17%) of the target stimuli appeared without a cue (no cue), 224 (67%) appeared in the same rectangle as the cue (valid cue), and 56 (17%) appeared in the rectangle opposite to the cue (invalid cue). Mean reaction time (RT) and corresponding errors was calculated for each stimuli type. Total task duration was nine minutes and 20 sec. In addition, relevant background information was obtained in a questionnaire. Results: Linear mixed model analyses showed that higher V̇O2max was associated with faster RT for stimuli following invalid cue (Estimate=-2.69, SE=1.03, p=.011), and for stimuli following valid cue (Estimate=-2.08, SE=1.03, p=.048). There was no association of muscle mass and stimuli (F=1.01, p=.397) or of weekly training and stimuli (F=.99, p=.405). Conclusion: The results suggest that cardiorespiratory fitness is associated with cognitive performance in healthy male high-school students in the executive domains of selective attention.